2014
DOI: 10.4172/jcalb.1000120
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Stress, Leisure Time Vigorous Physical Activity and Depressive Symptoms in Adolescents

Abstract: Background: This study investigated the association between stress, leisure-time vigorous physical activity (LVPA) and depressive symptoms in adolescents 13-18 years. The stress moderating role of LVPA was also investigated. Clarification of the role of physical activity in relation to stress and mental health can be used to form health promoting interventions to strengthen adolescent development. Methods:The sample consisted of n = 1183 students from public schools in Mid-Norway (age groups: 13-14 years, 15-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Perhaps they felt that the strain related to vigorous activities is inherent to these activities, and are not related to the time of year. Various studies, however, found that engaging in vigorous activities is positively related to children's emotional well-being (Henning Brodersen, Steptoe, Phil, Williamson, & Wardle, 2005;Moksnes, Lillefjell, & Espnes, 2013). Yet, based on an extensive literature review, showing contradicting results, Strong et al (2005) concluded that there is insufficient evidence to conclude whether vigorous activities have positive or negative ramifications on children's psychosocial factors.…”
Section: Discussionmentioning
confidence: 97%
“…Perhaps they felt that the strain related to vigorous activities is inherent to these activities, and are not related to the time of year. Various studies, however, found that engaging in vigorous activities is positively related to children's emotional well-being (Henning Brodersen, Steptoe, Phil, Williamson, & Wardle, 2005;Moksnes, Lillefjell, & Espnes, 2013). Yet, based on an extensive literature review, showing contradicting results, Strong et al (2005) concluded that there is insufficient evidence to conclude whether vigorous activities have positive or negative ramifications on children's psychosocial factors.…”
Section: Discussionmentioning
confidence: 97%